Recovery of Cationic Dyes Bearing Wastewater Using Shea Butter Leaves: Kinetic Adsorption, Desorption and Reusability Studies - Shehu, M-B Ayuba, B (University of Eloued جامعة الوادي, 2023)
The present study explains the preparation and application of Vitellaria paradoxa Activated Carbon (VPAC) as a new low-cost adsorbent in the removal of methylene blue and rhodamine B dye from its aqueous solution. SEM showed surface morphology, EDX disclosed elemental composition while pHpzc determines the pH at which the adsorbent surface has net electrical neutrality. The effects of operating parameters such as contact time, adsorbent dose, initial dye concentration, pH, temperature and competition were investigated for the removal of methylene blue and rhodamine B dyes using VPAC. VPAC was maximum at pH of 6 contact time of 60min and pH of 7 contact of time 80min respectively. The adsorption kinetic results showed that the pseudo-second order model was more suitable to explain the adsorption of methylene blue and rhodamine Bdye onto VPAC, because the calculated and experimental are in agreement. In VPAC, Qexp = 49.092mg/g, Qcal = 49.505mg/g and R2= 0.999 for methylene blue while Qexp = 49.508mg/g, Qcal = 49.011mg/g and R= 0.999 for rhodamine B. The adsorption mechanism results showed that the adsorption process was controlled by both the internal and external diffusion of methylene blue and rhodamine B dye molecules. Desorption studies for reusability revealed that HCl offered the best recovery.
Article
Keywords: Adsorption; Desorption; reusability; recovery; vitellaria paradoxa